ANALISIS LITERASI MEMBACA SISWA KELAS 5 SD NEGERI 2 PLANTARAN KABUPATEN KENDAL MELALUI BUKU CERITA YANG BERORIENTASI PADA PROFIL PELAJAR PANCASILA - Ashari, Ayu; Soegeng, A.Y.; Mudzanatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background that drives this research is the lack of interest in reading in students and the lack of reading motivation, which is based on the results of the interviews, there is no poster that provides motivation for the spirit of reading for literacy in the classroom only in the library which should also be in the classroom. So that students are less motivated and the storybooks in the classroom are still few So sometimes students bring their favorite books from home. The purpose of this study is based on the question in the formulation of the problem, namely to be able to find out the implementation of reading literacy for Grade 5 students of SD Negeri 2 Plantaran through the medium of storybooks oriented to the Pancasila Student Profile. Be able to find out what difficulties can affect the literacy of 5th grade students of SD Negeri 2 Plantaran. This type of research is using a descriptive qualitative research method that refers to an approach that produces data in the form of descriptive data. His research is based on phenomena based on observations in written, oral form from the subject and the object of research. Based on the results of this study, the suggestion that can be conveyed is to analyze the reading literacy of 5th grade students of SD Negeri 2 Parque. Kendal Regency through storybooks oriented to the Pancasila Student Profile can be used as one of the alternative teachers in school literacy activities